Pengaruh Penatausahaan Aset Tetap Peralatan dan Mesin Terhadap Pengamanan Aset Tetap Peralatan dan Mesin pada Dinas Pemerintah Kota Bandung - Caroline, Sheren Audia; Gunawan, Arwan (Indonesian Accounting Research Journal, 2025)
This research aims to determine how much the effect of Equipment and Machinery Assets Administration on Equipment and Machinery Assets Security at Dinas inBandung Government City. The population of this research is 21 Dinas in Bandung Government City, with purposive sampling of 2 goods management employees from each Dinas with the number of respondents being 42 people. This research is quantitative with a quantitative descriptive approach. Data obtained from questionnaires with simple linear regression analysis using SPSS version 25. The results of this research show that the equipment and machinery assets administration has a significant and positive effect that is 34,5% on the equipment and machinery security.